The impact of grandparent-grandchild interactions on the imagination of aging among Chinese youth groups: The chain mediating role of intergenerational relations and filial piety concept - Xiaojuan Hu; Fen Xie (PLoS ONE, 2026)
Centered on respecting elders and intergenerational responsibility, Confucian filial piety culture serves as a core cultural norm in Chinese society. This study integrates this cultural framework with the context of China’s rapid population aging to explore how grandparent-grandchild interactions within Chinese families shape young adults’ aging imagination. Based on a survey of 778 Chinese youth aged 18–35, the findings show that both daily and ritualistic interactions positively predict young adults’ aging imagination, and daily interactions have a stronger predictive effect. Intergenerational relations and filial piety not only serve as independent mediators but also constitute a chain mediating pathway, indicating that emotional bonds and cultural values synergistically foster young people’s positive aging imagination. This study suggests that efforts to strengthen intergenerational interactions and integrate culturally rooted aging education are critical for promoting positive aging attitudes among youth.